Asymmetric 1,4-bis(ethynyl)bicyclo[2.2.2]octane rotators via monocarbinol functionalization. Ready access to polyrotors - Lemouchi, Cyprien; Batail, Patrick (Beilstein Journal of Organic Chemistry, 2015)
Asymmetric rotators with a 1,4-bis(ethynyl)bicyclo[2.2.2]octane (BCO) core are needed for engineering crystalline arrays of functional molecular rotors. Their synthesis uses carbinol, 2-methyl-3-butyn-2-ol, as a protecting group because of its polar character and its ability to sustain orthogonal functionalization with the further advantage of being readily removed. The synthesis in good yields of unprecedented asymmetric rotors and polyrotors demonstrates the efficiency of this strategy.
Keywords: bridging ligands; molecular rotors; polyrotors